Peptidolipid as binding site of acetylcholinesterase molecular recognition of paraoxon in Langmuir films - Wang, Chengshan (Langmuir : the ACS journal of surfaces and colloids, 2006)
Peptidolipid C18H35O (stearoyl)-Phe-Trp-Ser-His-Glu (peptidolipid A) was synthesized and spread at the air-water interface to study the interaction with an organophosphorus compound. Paraoxon, sodium dihydrogen phosphate, or 4-nitrophenyl phosphate disodium was added to the subphase, but only paraoxon changed the surface pressure-area (pi-A) isotherm of peptidolipid A. This indicated a specific interaction between paraoxon and peptidolipid A. To clarify which amino acid residue of peptidolipid A was responsible for the interaction, peptidolipid B, namely, C18H35O-Gly-His-Ser-Glu-Glu, was synthesized and studied as a Langmuir film. The difference between the pi-A isotherms of peptidolipid B in the absence and presence of paraoxon in the subphase was minimal; consequently, the presence of amino acids phenylalanine (Phe) and tryptophan (Trp) in peptidolipid A may explain the interaction between peptidolipid A and paraoxon. The compression-decompression cycles and kinetic studies of peptidolipid A showed that the Langmuir film was stable. The in situ optical properties of the peptidolipid A Langmuir film such as UV-vis and fluorescence spectroscopies were examined to elucidate the interaction between peptidolipid A and paraoxon. UV-vis absorption of peptidolipid A was investigated in the presence and absence of paraoxon in the subphase. The emission maximum of fluorescence of Trp in peptidolipid A was observed at 351 nm on pure water, and the band intensity decreased when the concentration of paraoxon increased in the subphase. This suggested that the Trp was involved in the molecular recognition process. Epifluorescence micrographs showed domains of peptidolipid A on the pure water subphase. In the presence of paraoxon in the subphase, the Langmuir film of peptidolipid A showed a homogeneity, which was another indication of the recognition between paraoxon and peptidolipid A